Fueling the Bio-economy: European Culture Collections and Microbiology Education and Training. Issue 2 (February 2016) - Antunes, André; Stackebrandt, Erko; Lima, Nelson
Abstract : A survey of European Microbial Biological Resource Centers and their users provided an overview on microbiology education and training. The results identified future increases in demand despite several shortcomings and gaps in the current offer. Urgent adjustments are needed to match users' needs, integrate innovative programs, and adopt new technologies.